The effects of watching English and Malay subtitled English movie on ESL students' English vocabulary / Wafa Omar - Omar, Wafa (2015)
The study examines on the effects of watching English and Malay subtitled English movie on ESL students' English vocabulary. The objectives of the study are to determine whether ESL students' English vocabulary is affected when watching English and Malay subtitled English Movie and to identify whether the degree of improvement of ESL students' English vocabulary is affected when watching English and Malay subtitled English movie. The study used a one-shot case study method. Samples from the study were taken from seventy-two Universiti Teknologi Mara, Lendu, Melaka students who were randomly selected. They were equally divided into two groups; English subtitles group and Malay subtitles group. Paired sample t-test is used to analyse the data taken from students' performance scores. The result of the study revealed the ESL students' English vocabulary was significantly affected after they were exposed to English (t (35) =7.76, p=0.00) and Malay subtitled (t (35) = 5.19, p=0.00) English movie. However, students from English subtitles group (160 differences) obtained a higher degree of improvement compared to the Malay subtitles group (101 differences). The English subtitles group obtained higher mean differences and higher degree of improvement as they could listen and read the vocabulary at the same time. Moreover, they could verify if they heard exactly the same vocabulary as what they interpreted. The research will benefit ESL students, lecturers and teachers on how English vocabulary can be developed by using subtitled English movies.